Inovasi Media Digital Storytelling Islami: Pengembangan Kisah Nabi Yusuf untuk Menumbuhkan Nilai Kesabaran Anak Usia Dini - Maiva Wulandari; Veryawan Veryawan; Saptiani Saptiani (Universitas Islam Negeri Sumatera Utara, 2026)
Instilling the value of patience in early childhood is often difficult to understand due to its abstract nature. Therefore, interesting and concrete learning media are needed for children. This study aims to develop a storytelling learning media based on the story of the Prophet Yusuf to instill the value of patience in early childhood. This study adopted a Research and Development (R&D) model. The subjects were students of Al-Azhar Kindergarten in Langsa City, while the object was the storytelling media. The research instruments included observation sheets and expert questionnaires. Data were analyzed descriptively with qualitative and quantitative approaches. The results showed that digital animated storytelling media successfully increased children's understanding of the value of patience through activities such as watching stories, quizzes, and puzzles. Therefore, early childhood teachers recommend the use of digital storytelling media as an alternative learning medium to instill religious and moral values with a more interesting and effective approach.